Health information system (HMS) in Malaysia - Ujan, Imran Anwar; Shah, Asadullah; Bhutto, Arifa; Imtiaz Ali, Najma (Asia Pacific Institute of Advanced Research (APIAR), 2018)
The wide reserves in Information Technology have contributed to its gradual importance. Societies have benefited from its progress. Moreover, technology has greatly influenced the satisfaction of patients and the quality of hospitals. The influence of technology has given distinct benefit to I, unique from other factors that can also contribute the original presentation. The benefits of technology may also be recognized in the long run by hospitals. The study gives suggestions on how to relate IT investments to performance and its effect when partnered with technology. The study also control variables in the analysis. The result of the study provide support for the IT connection observed after given time lags. Such a relation may not be present in cross-sectional or snapshot data analysis. Moreover, results imply the support of the effects of technology that depend on by hospitals.